Seventy‐five Years of Improvement of Yield and Agronomic Traits of Soybean Cultivars Released in the Yellow‐Huai‐Hai River Valley. Issue 5 (1st September 2016) - Wang, Caijie; Wu, Tingting; Sun, Shi; Xu, Ran; Ren, Jianjun; Wu, Cunxiang; Jiang, Bingjun; Hou, Wensheng; Han, Tianfu
Abstract : Yellow‐Huai‐Hai River Valley (YHH) in China has a long history of soybean [ Glycine max (L.) Merr.] breeding. The genetic improvement of yield and agronomic traits of soybean cultivars due to breeding is rarely documented. The objectives were to analyze the trend of changes on widely‐grown soybean cultivars in this region. Twenty‐five soybean cultivars released over the period from 1929 until 2004 were selected. The field trial was conducted in three locations in 2 yr (2009–2010) and one location in 2011. Linear, bilinear, and quadratic regression models were built and compared to determine the rate of change for each trait. The yield gain was 9.97 kg ha –1 yr –1 during the eight decades. Current cultivars had shorter plant height, fewer nodes, higher lodging resistance, fewer pods per plant, fewer seeds per plant, more seeds per pod, higher 100‐seed weight (100‐SW) and higher yield than ancestral cultivars. The changing rates of these traits were either constant or variable with linear or quadratic models. Plant height (PH), height of the lowest pod (HLP), and seeds per pod (SPPOD) of new cultivars were more stable across environments than old cultivars, whereas lodging score (LS) and yield were less stable across environments. Yield increase was mainly attributed to an increase in SPPOD and seed weight rather than pods per plant (PPP). Collectively, improvements in agronomic and yield traits were significant during the 75‐yr‐long breeding effort. This study also shed light on developing future breeding strategies in the YHH.